Application of Ling Tien Kung Movement Technique in Reducing Diabetes Mellitus in Elderly - Nyna Puspita Ningrum; Retno Setyo Iswati; Indria Nuraini (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Diabetes Mellitus (DM) in the elderly is a disease with blood glucose levels increasing from the normal value affected by the insulin hormone. As the age increases, the risk of DM increases, due to a decrease in physiology and biochemistry in the body's system. Therapy or solutions that can be done to overcome diabetes in the elderly can be done pharmacological or non-pharmacological. One of the non-pharmacological therapies is by doing the Ling Tien Kung movement. The Ling Ting Kung movement is a therapy centered on anal training, "empet-empet anus" and "tiptoeing". The general objective of this research was to determine the results of the Application of Ling Tien Kung Movement Technique in Reducing Diabetes Mellitus in the Elderly. This research method is quantitative analytical research with the approach of one group pretest post-test design.